Islamic law - Aziz Al - Azmeh (ed.) (London, 1988)
This book underlines the mutability of Islamic law and attempts to relate its substantive and institutional varieties and transformations to social, political, economic and other historical circumstances. The studies in the book range from discussion of the received wisdom in Islamic law to studies of legal institutions and the theoretical means employed by Islamic law for the accommodation of changing his torical circumstances.
Keywords: Islamic law